In-sacco degradability of different protein fractions - ICHHPONANI, J; WADHWA, M; KATRAIA, P; MAKKAR, G S (The Indian Journal of Animal Sciences, 2013)
The animal (6) and plant protein supplements (8) were fractionated into soluble and insoluble proteins and their in-sacco degradahility assessed at different incubation intervals in an adult mmen-fistulated buffalo. In spite of the higher CP in the animal protein supplements (APS) than plant protein supplements (PPS), the 48 hr rumen degradability was considerably low in the former than in the letter. The low rapidly soluble fraction and potentially degradable fractions in APS than in PPS resulted in significantly higher proportion of undegradable fractions in the former than in the latter. The effective degradability and degradation rate of protein supplements could be predicted by determining the prolamin and glutelin contents in the test samples and by fining their respective values in the simple or multiple regressionequations.